Nuclear fission properties of super heavy nuclei described within the four-dimensional Langevin model - Ishizuka, Chikako; Zhang, Xuan; Shimada, Kazuya; Usang, Mark; Ivanyuk, Fedir; Chiba, Satoshi (Frontiers in Physics, 2023)
Understanding the fission properties of super-heavy nuclei (SHN) is essential not only for the synthesis of new elements but also for astrophysical nucleosynthesis because fission fragments from SHN are recycled as the seed nuclei of the r-process. A recent discovery of the r-process site by the gravitational wave observations requires more precise nuclear information for the detailed simulation of the r-process nucleosynthesis. However, the fission mechanisms of the SHN are not understood well, and therefore theoretical predictions of distributions of the fission fragments of SHN are very model-dependent. Our four-dimensional Langevin model can calculate various properties of the fission fragments, such as the distribution of fission yields, kinetic energies, and deformation of fission fragments and their correlations just after scission. Those results are consistent with the experimental data, especially in the actinide region without adjusting parameters. Based on such a reliable model, we previously investigated the fission of representative SHN where the experimental data exist and found that doubly-magic shell closure of 132Sn and 208Pb dominates the fission process. This paper demonstrates the results of our calculations for the systematics of fission yield and the total kinetic energies from the neutron-rich to the neutron-deficient side of SHN. We also show the decomposition of fission modes, such as standard/super-long/super-short modes, based on a Brosa-like concept.